Analysis of differential expression of protease-activated receptors in patients with allergic fungal rhinosinusitis. (April 2018) - Sawhney, Shikhar; Bansal, Sandeep; Kalyan, Madhur; Verma, Indu; Singh Virk, Ramandeep; Gupta, Ashok Kumar
Background: Ever since its characterization in the 1970s, allergic fungal rhinosinusitis (AFRS) has been the subject of much controversy, especially regarding its pathogenesis. In this study, we analyzed the differential expression of genes that encode protease-activated receptors (PAR) in patients with AFRS and patients with chronic rhinosinusitis, and tried to understand the pathogenic basis of this disease. Objective: To analyze the differential expression of PAR genes in patients with AFRS and in patients with chronic rhinosinusitis. Methods: Mucosa from ethmoid sinuses of 51 patients (tests and controls) was biopsied and evaluated for messenger RNA expression of PAR genes by using reverse transcriptase–polymerase chain reaction. Each of the four PAR genes, i.e., par1, par2, par3 and par4 was amplified, the final gene products were run on 1.8% agarose gel and analyzed by densitometry to calculate differential expression. The significance level was determined as p ≤ 0.05. Results: It was observed that the expressions of all four par genes were higher in the test samples compared with the controls, but statistical significance was achieved only for par1 (p=0.004) and par2 (p=0.05). Comparative expression of the four PAR genes was also performed within the test and control groups, and a statistically significant difference was seen between par1 and par2 (p=0.007), par1 and par3 (p=0.029), par1 and par4 (p=0.0001), par2 and par4 (p=0.002), and par3 and par4 (p=0.009) in the test group. In the control group as well, par1, par2, and par3 exhibited a higher expression compared with par4 but the difference was significant between par3 and par4 genes only. Conclusion: Patients with AFRS expressed increased levels of PAR genes in their nasal mucosa, and, of the four PAR genes, a higher expression of par1, par2, and par3 was observed in both the groups compared with par4. This information contributes toward our understanding of pathogenesis and possibly treatment of AFRS.